Microleakage of Composite Restorations Following Chemo-mechanical and Conventional Caries Removal - SM. Mousavinenasab; M. Jafary (Tehran University of Medical Sciences, 2004)
Statement of Problem: Microleakage is the most important factor in composite restorations failure, resulting in marginal degradation, marginal staining, secondary caries and pulp damage. One of the factors that influence microleakage is the method of caries removal. Convention rotary instrumentation generates smear layer on the dental surface, whereas chemo-mechanical caries removal increases surface roughness. Purpose: The aim of this study was to compare the microleakage of composite restorations following caries removal via conventional versus chemo-mechanical methods. Materials and Methods: One hundred class V carious human posterior teeth were randomly divided into two equal groups. Caries were completely removed with carbide burs in group one and according to manufacturer's instruction in chemo-mechanical group (Carisolv group or group two). Then the same composite restorative material, followed by finishing and polishing, filled all the cavities. Subsequently the specimens were thermocycled and then placed in dye solution. The teeth were sectioned through the restorations and evaluated for microleakage scores using a stereomicroscope. The data were analyzed using Mann-Whitney-U test. Results: Prevalence of scores 0 and 1 of microleakage in occlusal margins in group one was 80% and 20%, respectively and in group two 74% and 36%, respectively. Prevalence of scores 0, 1 and 2 of microleakage in gingival margins in group one was 56%, 36% and 8%, respectively and 42%, 42% and 16% in group two, respectively. Scores 3 and 4 of microleakage were not seen in any of the groups. Statistical analysis showed significant difference in microleakage between occlusal and gingival margins in each group (P0.05). Conclusion: The results from this study indicate no significant difference in microleakage between conventional and chemo-mechanical caries removal methods.